In Vivo Imaging of Glial Activation after Unilateral Labyrinthectomy in the Rat: A [18F]GE180-PET Study - Zwergal, Andreas; Günther, Lisa; Brendel, Matthias; Beck, Roswitha; Lindner, Simon; Xiong, Guoming; Eilles, Eva; Unterrainer, Marcus; Albert, Nathalie Lisa; Becker-Bense, Sandra; Brandt, Thomas; Ziegler, Sibylle; et al. (Frontiers in Neurology, 2017)
The functional relevance of reactive gliosis for recovery from acute unilateral vestibulopathy is unknown. In the present study glial activation was visualized in vivo by [18F]GE180-PET in a rat model of unilateral labyrinthectomy and compared to behavioural vestibular compensation over time. 14 Sprague-Dawley rats underwent a unilateral labyrinthectomy by transtympanic injection of bupivacaine/arsenilate, 14 rats a SHAM unilateral labyrinthectomy (injection of normal saline). Glial activation was depicted with [18F]GE180-PET and ex vivo autoradiography at baseline and 7, 15, 30 days after unilateral labyrinthectomy/ SHAM unilateral labyrinthectomy. Postural asymmetry and nystagmus were registered at 1, 2, 3, 7, 15, 30 days after unilateral labyrinthectomy/ SHAM unilateral labyrinthectomy. Signs of vestibular imbalance were found only after unilateral labyrinthectomy, which significantly decreased until days 15 and 30. In parallel, [18F]GE180-PET and ex vivo autoradiography depicted glial activation in the ipsilesional vestibular nerve and nucleus on days 7 and 15 after unilateral labyrinthectomy. Correlation analysis revealed a strong negative association of [18F]GE180 uptake in the ipsilesional vestibular nucleus on day 7 with the rate of postural recovery (r = -0.90, p < 0.001), suggesting that glial activation accelerates vestibular compensation. In conclusion, glial activation takes place in the ipsilesional vestibular nerve and nucleus within the first 30 days after unilateral labyrinthectomy in the rat and can be visualized in vivo by [18F]GE180-PET.